Response of nitrate leaching to no‐tillage is dependent on soil, climate, and management factors: A global meta‐analysis. Issue 8 (9th February 2023) - Li, Jinbo; Hu, Wei; Chau, Henry Wai; Beare, Mike; Cichota, Rogerio; Teixeira, Edmar; Moore, Tom; Di, Hong; Cameron, Keith; Guo, Jing; Xu, Lingying
Abstract: No tillage (NT) has been proposed as a practice to reduce the adverse effects of tillage on contaminant (e.g., sediment and nutrient) losses to waterways. Nonetheless, previous reports on impacts of NT on nitrate ( NO 3 − ) leaching are inconsistent. A global meta‐analysis was conducted to test the hypothesis that the response of NO 3 − leaching under NT, relative to tillage, is associated with tillage type (inversion vs non‐inversion tillage), soil properties (e.g., soil organic carbon [SOC]), climate factors (i.e., water input), and management practices (e.g., NT duration and nitrogen fertilizer inputs). Overall, compared with all forms of tillage combined, NT had 4% and 14% greater area‐scaled and yield‐scaled NO 3 − leaching losses, respectively. The NO 3 − leaching under NT tended to be 7% greater than that of inversion tillage but comparable to non‐inversion tillage. Greater NO 3 − leaching under NT, compared with inversion tillage, was most evident under short‐duration NT (<5 years), where water inputs were low (<2 mm day −1 ), in medium texture and low SOC (<1%) soils, and at both higher (>200 kg ha −1 ) and lower (0–100 kg ha −1 ) rates of nitrogen addition. Of these, SOC was the most important factor affecting the risk of NO3 − leaching under NT compared with inversion tillage. Globally, on average, the greater amount of NO3 − leached under NT, compared with inversion tillage, was mainly attributed to corresponding increases in drainage. The percentage of global cropping land with lower risk of NO3 − leaching under NT, relative to inversion tillage, increased with NT duration from 3 years (31%) to 15 years (54%). This study highlighted that the benefits of NT adoption for mitigating NO 3 − leaching are most likely in long‐term NT cropping systems on high‐SOC soils. Abstract : A global meta‐analysis was conducted to test the hypothesis that effects of no tillage (NT) on nitrate ( NO 3 − ) leaching losses depend on their comparison to tillage form and are moderated by environment factors. Results showed that NO 3 − leaching under NT was greater than that of inversion tillage but comparable to non‐inversion tillage, and yield‐scaled NO 3 − leaching was affected more by NT than area‐scaled NO 3 − leaching. Our study suggests an increased risk of NO 3 − leaching under short duration NT on low‐SOC soils, but potential mitigation of NO 3 − leaching losses from long‐term NT cropping systems on high‐SOC soils compared to inversion tillage.